Fuel Economy Standards and Public Transport - Julius Berger; Waldemar Marz (Center for Economic Studies and ifo Institute (CESifo), 2024)
We identify and examine a novel welfare channel of fuel economy standards through the in-teraction with public transit and households' location choices. A stricter emission standard for cars decreases the marginal cost of driving and triggers a shift in modal choice from public to private transport and a rise in carbon emissions. In the long run, the modal shift exacerbates the increase in the average commute length that results from lower driving costs, as well as traffic congestion. The annual welfare cost for a 50 percent emission reduction goal in a setting calibrated with U.S. data turns out 8 percent (equiv. to 54 USD p.c.) higher than when neglecting public transport. With a larger role of public transport as in Europe, this effect rises to 12 percent (equiv. to 83 USD p.c.). An alternative fuel tax policy, by contrast, induces a modal shift towards public transport and reduces the average commute, urban congestion and the welfare cost of emission reductions.
Keywords: H23; Q48; R13; R48; 330; fuel economy standards; public transport; monocentric city; fuel tax; carbon emissions